Linear normal stress under a wheel in skid for wheeled mobile robots running on sandy terrain. (April 2017) - Guo, Junlong; Gao, Haibo; Ding, Liang; Guo, Tianyou; Deng, Zongquan
Highlights: Experimental and theoretical research was made for wheels in longitudinal skid. Both wheel sinkage and normal stress can be expressed using a quadratic equation. Radial stress can be given linearly using wheel sinkage with a constant named sand stiffness. Abstract: Wheeled mobile robots are often used on high risk rough terrain. Sandy terrains are widely distributed and tough to traverse. To successfully deploy a robot in sandy environment, wheel-terrain interaction mechanics in skid should be considered. The normal and shear stress is the basis of wheel-soil interaction modeling, but the normal stress in the rear region on the contact surface is computed through symmetry in classical terramechanics equations. To calculate that directly, a new reference of wheel sinkage is proposed. Based on the new reference, both the wheel sinakge and the normal stress can be given using a quadratic equation as the function of wheel-soil contact angle. Moreover, the normal stress can be expressed as a linear function of the wheel sinkage by introducing a constant coefficient named as sand stiffness in this paper. The linearity is demonstrated by the experimental data obtained using two wheels and on two types of sands. The sand stiffness can be estimated with high accuracy and it decreases with the increase of skid ratio due to the skid-sinkage phenomenon, but increases with the increase of vertical load. Furthermore, the sand stiffness can be utilized directly to compare the stiffness of various sandy terrains.